Do Athlete Identification and Shoe Design Mitigate Perceived Injury Risk in Nike KD Low-Top? - Wildan Guretno Prasetiyo; Ridho Riadi Akbar; Debi Irawan; Rama Chandra Jaya; Arie Hendra Saputro; Muhamad Addin Al Haadi (Jurnal Manajemen dan Kewirausahaan, 2026)
Despite rising NBA Achilles injuries linked to low-top shoes, models like the Nike KD series continue to enjoy massive commercial success. This study investigates this paradox by examining whether athlete identification and aesthetic shoe design override perceived injury risk in shaping purchase intention. Using a quantitative correlational design, data were collected from 300 basketball enthusiasts in Indonesia, purposively selected for their interest in the NBA and awareness of Kevin Durant. Results confirm that athlete identification and aesthetic design directly drive purchase intention, whereas perceived injury risk acts as a significant deterrent. Notably, moderation analysis reveals that safety concerns attenuate the emotional drive of athlete identification but unexpectedly amplify the influence of aesthetic design. Consequently, while athlete identification is the primary driver, aesthetic design becomes paramount when injury risk is taken into account. This indicates that consumers actively repurpose risky low-tops into casual streetwear, prioritizing visual appeal over performance. Therefore, sportswear manufacturers should market low-top models as lifestyle apparel while improving their structural integrity.